Respuesta :

The equation is [tex]y = $72.99 + $28.45(x - 1)[/tex], where y is the monthly charge and x is the month in which it is calculated.

Step-by-step explanation:

Step 1:

First, we need to establish a relation between the difference in costs. For the first month it cost $72.99, during the second month, it costs $101.44 and in the third month, it costs $129.89. Difference in rates

Second months rate - First months rate = [tex]101.44 -72.99 = 28.45[/tex]

Third months rate - Second months rate = [tex]129.89 - 101.44 = 28.45.[/tex]

So for every consecutive month, the charges increase by $28.45

Step 2:

Now we develop an equation,

[tex]y = 72.99 + 28.45(x - 1)[/tex], where y is the charge that month and x is the month in which it is calculated.

For x = 1, [tex]y = $72.99 + $28.45(1 - 1) = $72.99 + $28.45(0) = $72.99,[/tex]

For x = 2, [tex]y = $72.99 + $28.45(x - 1) = $72.99 + $28.45(2 - 1) = $101.44,[/tex]

For x = 3, [tex]y = $72.99 + $28.45(3 - 1) = $72.99 + $28.45(3-1) = $129.89.[/tex]

So this is the equation to calculate the cost y the mobile provider charges in month x.